The Potential of Cold Atmospheric Pressure Plasmas for the Direct Degradation of Organic Pollutants Derived from the Food Production Industry - Cyganowski, Piotr; Terefinko, Dominik; Motyka-Pomagruk, Agata; Babinska-Wensierska, Weronika; Khan, Mujahid Ameen; Klis, Tymoteusz; Sledz, Wojciech; Lojkowska, Ewa; Jamroz, Piotr; Pohl, Pawel; Caban, Magda; Magureanu, Monica; et al. (Molecules (Basel, Switzerland), 2024)
Specialized chemicals are used for intensifying food production, including boosting meat and crop yields. Among the applied formulations, antibiotics and pesticides pose a severe threat to the natural balance of the ecosystem, as they either contribute to the development of multidrug resistance among pathogens or exhibit ecotoxic and mutagenic actions of a persistent character. Recently, cold atmospheric pressure plasmas (CAPPs) have emerged as promising technologies for degradation of these organic pollutants. CAPP-based technologies show eco-friendliness and potency for the removal of organic pollutants of diverse chemical formulas and different modes of action. For this reason, various types of CAPP-based systems are presented in this review and assessed in terms of their constructions, types of discharges, operating parameters, and efficiencies in the degradation of antibiotics and persistent organic pollutants. Additionally, the key role of reactive oxygen and nitrogen species (RONS) is highlighted. Moreover, optimization of the CAPP operating parameters seems crucial to effectively remove contaminants. Finally, the CAPP-related paths and technologies are further considered in terms of biological and environmental effects associated with the treatments, including changes in antibacterial properties and toxicity of the exposed solutions, as well as the potential of the CAPP-based strategies for limiting the spread of multidrug resistance.